Inside Back Cover: Segmented Polyurethane Elastomers with Mechanochromic and Self‐Strengthening Functions (Angew. Chem. Int. Ed. 15/2021). Issue 15 (4th February 2021) - Seshimo, Kota; Sakai, Hio; Watabe, Takuma; Aoki, Daisuke; Sugita, Hajime; Mikami, Koichiro; Mao, Yuchen; Ishigami, Akira; Nishitsuji, Shotaro; Kurose, Takashi; Ito, Hiroshi; Otsuka, Hideyuki
Abstract : Mechanofunctional polymers that exhibit color change, fluorescence, and self‐strengthening ability were developed by Hideyuki Otsuka et al. in their Communication on page 8406 . It is the first example of force‐induced cross‐linking reactions achieved by only the extension or compression of a bulk film. The cross‐linking reaction can be visualized via color change and fluorescence and evaluated by electron paramagnetic resonance spectroscopy.